Răspuns :
Răspuns:
Explicație pas cu pas:
a = rad(5) * (4rad(2) - 3rad(5)) - 2(2rad(10) + 3)
a = 4rad(10) - 3 rad(25) - 4rad(10) - 6
a = -3*5 - 6 = -15 - 6 = -21
c = 2rad(3) - (4rad(2) - 3rad(3)) - 4(7 + 2rad(6))
c = 8rad(6) - 6rad(9) - 21 - 8rad(6)
c = -6*3 - 28
c = - 18 - 28
c= -46
[tex]\it a= \sqrt5\cdot(4\sqrt2-3\sqrt5) -2\cdot(2\sqrt{10}+3) =4\sqrt{10}-15-4\sqrt{10}-6=-21\in\mathbb{Q}\\ \\ \\ c=\sqrt{12}\cdot(\sqrt{32}-3\sqrt3) -4(7+2\sqrt6) = \sqrt{384}-3\cdot\sqrt{36}-28-8\sqrt6 =\\ \\ =\sqrt{6\cdot64} -18-28-8\sqrt6=8\sqrt6-46-8\sqrt6=-46\in\mathbb{Q}[/tex]